How to make global supply chains more resilient - Gary Gereffi (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
Governments and companies play mutually supportive roles in building resilient global supply chains. This article identifies four post-pandemic managerial strategies and five government policies to enhance strategic competitiveness and develop workforce skills for 21st-century development.
Keywords: 330